995. A Murine Model of Klebsiella pneumoniae Gastrointestinal Colonization with Parenteral Vancomycin Administration. (4th December 2021) - Cheung, Bettina; Lebrun-Corbin, Marine; Hauser, Alan R
Abstract: Background: As a leading cause of nosocomial infections, Klebsiella pneumoniae poses a significant threat due to its propensity to acquire resistance to many classes of antibiotics, including carbapenems. Gastrointestinal (GI) colonization by K. pneumoniae is a risk factor for subsequent infection as well as transmission to other patients. To study this crucial step in pathogenesis, we developed a mouse model of K. pneumoniae GI colonization using a clinically relevant parenteral antibiotic regimen. Methods: To improve the clinical relevance of our model, we elected to use intraperitoneal injections of vancomycin, one of the most highly utilized antibiotics in the United States. Results: To optimize dosage in C57bl/6 mice, we injected 20mg/kg, 350mg/kg, or vehicle (PBS) for three days prior to gastric gavage with 10 8 colony forming units (CFU) of a low-resistance strain of K. pneumoniae . The mice who received 350mg/kg (a mouse equivalent of a human dose of 1g/day calculated through the FDA guidelines for estimating safe dosing) shed about 10 7 CFU/g of feces at Day 7 while those receiving the lower dose or vehicle shed 10 4 CFU/g. Next, we compared 3- or 5-day pre-treatments with vancomycin prior to inoculation with an ST258 (epidemic carbapenem-resistant) strain. At Day 7 post-inoculation, mice who received 5 days shed 10 10 CFU/g feces while those who received vancomycin for 3 days or vehicle for 5 days (PBS) shed 10 6 or 10 4 CFU/g feces respectively. Thus, we chose 5 days of 350mg/kg vancomycin injection as our regimen for inducing robust GI colonization in mice. Finally, we tested the durability of colonization by following fecal shedding in mice up to Day 60 post-inoculation with a second ST258 strain. Shedding during the first 7 days occurs at about 10 10 CFU/g feces, and from day 14 to day 60 fecal loads are stable around 10 7 CFU/g feces. Results are comparable between male and female mice. Conclusion: In conclusion, we have developed a mouse model of robust, prolonged GI colonization with multiple strains of K. pneumoniae using controlled dosing of a clinically relevant antibiotic. This model may be used to study a key step in K. pneumoniae pathogenesis and infection prevention in the future. Disclosures: All Authors : No reported disclosures